Dresden files : The complete first season - Hackett, Jonathan; Blackthorne, Paul.; Cruz, Valerie, 1976-; Mann, Terrence; Beimler, Hans.; Wolfe, Robert Hewitt; Butcher, Jim, 1971-; Egan, Peter, 1947-; Robison, Michael; Mastras, George, 1966-; Contner, James A.; Walsh, Laurence (Screenwriter); et al. (Santa Monica, Calif. : Lionsgate, 2007)
Harry Dresden is a private detective who also happens to be a real wizard. Although he tries to be a regular guy, Harry finds himself helping the Chicago police solve inexplicable crimes and battle dark forces that lurk around the city streets. Harry deals in all matters of supernatural threats.
Disc one: Birds of a feather / written by Peter Egan ; directed by Michael Robison -- The Boone identity / written by George Mastras ; directed by Jim Contner -- Hair of the dog / written by Laurence Walsh ; directed by Michael Nankin -- Rules of engagement / written by Curtis Kheel ; directed by Michael Grossman. Disc two: Bad blood / written by Jack Bernstein ; directed by Rick Rosenthal -- Soul beneficiary / written by Peter Egan ; directed by Ken Girotti -- Walls / written by Robert Hewitt Wolfe & Hans Beimler ; directed by John Fawcett -- Storm front / written by Hans Beimler & Robert Hewitt Wolfe ; directed by David Carson. Disc three: The other dick / written by George Mastras ; directed by James Head -- What about Bob / written by David Simkins ; directed by David Straiton -- Things that go bump / written by Robert Hewitt Wolfe ; directed by Michael Grossman -- Second city / written by Barry Schkolnick ; directed by Nick Copus.
Title from container.
Developed by Hans Beimler & Robert Hewitt Wolfe.
Based on the novels by Jim Butcher.
Originally broadcast on television in 2007.
Contains all 12 episodes from the first season.
Special features: Audio commentaries; making-of featurette; deleted scenes.
Keywords: Dresden, Harry -- (Fictitious character) -- Drama; Wizards -- Illinois -- Chicago -- Drama; Private investigators -- Illinois -- Chicago -- Drama; Fantasy. -- Television series; Chicago (Ill.) -- Drama; Illinois -- Chicago; Television for the hearing impaired; DVD-Video discs; Video recordings for the hearing impaired; Television series; Fantasy television programs; Detective and mystery television programs; Television adaptations; Drama; Television programs; Mystery television programs